2020
DOI: 10.1109/access.2020.2994115
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Data Mining Method for Tunnel Engineering Based on Real-Time Monitoring Data From Tunnel Boring Machines

Abstract: Tunnel engineering is one of the typical megaprojects given its long construction period, high construction costs and potential risks. Tunnel boring machines (TBMs) are widely used in tunnel engineering to improve work efficiency and safety. During the tunneling process, large amount of monitoring data has been recorded by TBMs to ensure construction safety. Analysis of the massive real-time monitoring data still lacks sufficiently effective methods and needs to be done manually in many cases, which brings pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…According to the order from large to small, they are the regional climate environment, engineering hydrogeology, professional quality, safety awareness, and labor management, which belong to the cause factors, indicating that these factors are easy to affect other factors in the accident system. In the accident report, most of the causes of non-safety accidents are geological environment problems that are difficult to investigate [ 51 ], such as “It is inferred that the coupling effect of various unfavorable geological conditions and climatic reasons such as earthquake and sufficient rainfall into April is the main reason for the overall brittle damage and instantaneous and sudden local collapse of the vault.” and “After the accident, the accident investigation team expert group after site investigation, found that the geological conditions are actually striped mixed granite, lamellar development, the existence of kaolin and other unfavorable geological conditions of water softening”. The regional climate environment and engineering hydrogeology are the most significant factors affecting other factors, such as construction, design, and survey.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…According to the order from large to small, they are the regional climate environment, engineering hydrogeology, professional quality, safety awareness, and labor management, which belong to the cause factors, indicating that these factors are easy to affect other factors in the accident system. In the accident report, most of the causes of non-safety accidents are geological environment problems that are difficult to investigate [ 51 ], such as “It is inferred that the coupling effect of various unfavorable geological conditions and climatic reasons such as earthquake and sufficient rainfall into April is the main reason for the overall brittle damage and instantaneous and sudden local collapse of the vault.” and “After the accident, the accident investigation team expert group after site investigation, found that the geological conditions are actually striped mixed granite, lamellar development, the existence of kaolin and other unfavorable geological conditions of water softening”. The regional climate environment and engineering hydrogeology are the most significant factors affecting other factors, such as construction, design, and survey.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The performance of the proposed model in tunnel engineering based on the geological data is compared with the different conventional methods such as GPR-SVM [15], ANN [16], GCN-LSTM [17], DM [18], and M-KNN [19] in terms of performance metrics. Figure 3 displays the ROC curve, which was used to evaluate the proposed model's predictive capacity compared to traditional techniques.…”
Section: Performance Analysismentioning
confidence: 99%
“…The practical experience and previous studies indicated that the rotation speed (N), advance rate (V), and rotation speed of the screw machine (N s ) are the main operating parameters of the machine operators. Cutterhead thrust (F) and torque (T) indirectly reflect the interaction between the EPB machine and the excavation face, and torque of the screw machine (T s ) reflects the conditions of slag discharge [58,59]. Chamber pressure (C p ) can be used to evaluate the stability of the excavation face, and it is the representative parameter of EPB shield machine.…”
Section: Parameters Selectionmentioning
confidence: 99%